Uganda Economic Update, August 2013, Second Edition - World Bank (Washington, DC, 2014)
Despite the difficult past five year period, renewed macro-stability is creating a strong basis for Uganda to rebuild a more resilient economy. The economy is currently recovering and is estimated to have grown at a rate of approximately 5.0 percent in FY2013. This improved stability is creating an enabling environment for the implementation of long term fiscal and structural policies that may facilitate Uganda's achievement of accelerated growth and ultimately of its goal of achieving middle income status. An accelerated rate of economic growth can be achieved through a more rapid diversification of the economic base. Uganda has to manage this rapid structural transformation appropriately so that sufficient jobs will be created to provide employment for the young and rapidly growing working population and to promote the growth of the most productive sectors to sustain productivity gains and economic growth over time. This paper is organized in two parts as follows: part one gives Uganda's economy; and part two presents creating more productive employment opportunities for more of Uganda's citizens.